Fuzzy-set Case Studies. (August 2017) - Mikkelsen, Kim Sass
Contemporary case studies rely on verbal arguments and set theory to build or evaluate theoretical claims. While existing procedures excel in the use of qualitative information (information about kind), they ignore quantitative information (information about degree) at central points of the analysis. Effectively, contemporary case studies rely on crisp sets. In this article, I make the case for fuzzy-set case studies. I argue that the mechanisms that are the focal points of contemporary case study methods can be modeled as set-theoretic causal structures. I show how case study claims translate into sufficiency statements. And I show how these statements can be evaluated using fuzzy-set tools. This procedure permits the use of both qualitative and quantitative information throughout a case study. As a consequence, the analysis can determine whether one or more cases are both qualitatively and quantitatively consistent with its claims. Or whether some or all cases are consistent by kind but not by degree.